Novel Esomeprazole Magnesium-Loaded Dual-Release Mini-Tablet Polycap: Formulation, Optimization, Characterization, and In Vivo Evaluation in Beagle Dogs - Taek Kwan Kwon; Ji-Hyun Kang; Sang-Beom Na; Jae Ho Kim; Yong-Il Kim; Dong-Wook Kim; Chun-Woong Park (MDPI AG, 2022)
Esomeprazole magnesium (EMP) is a proton pump inhibitor (PPI) that reduces acid secretion. EMP has a short plasma half-life (approximately 1.3 h); hence, nocturnal acid breakthrough (NAB) frequently occurs, disturbing the patient's nighttime comfort and sleep. We aimed to develop a novel esomeprazole magnesium-loaded dual-release mini-tablet polycap (DR polycap) with a prolonged onset time and improved bioavailability to prevent NAB. The formulation of the EPM mini-tablet core resulted in rapid drug release. The core was coated with an inner coating and an Eudragit® L30D-55 aqueous dispersion coating to prepare the first-release mini-tablet. In addition, the core was coated with an inner coating and an aqueous dispersion of Eudragit® S100 and Eudragit® L100 coating to prepare the second-release mini-tablet. Each mini-tablet type was characterized using an in vitro dissolution test and microscopic examination. After testing, 10 of each mini-tablets were placed together in hard capsules to form DR polycaps. The combination of mini-tablets was optimized via in vitro release testing and in vivo pharmacokinetic studies. The AUC0-24h of the DR polycap was similar to that of a comparable commercial product (Nexium®); Cmax was lower by approximately 50%, and Tmax was extended by approximately 1.7-fold. In conclusion, DR polycap is an alternative to commercial products with improved NAB and dosing compliance because of its dual-release characteristics.